CONTENT-ANALYTICAL CHARACTERISTICS OF TAX DEBT IN UKRAINE - RUDENKO, Viktoriia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The substantiation of the essential content and the identification of trends in the growth/decrease of the tax debt is relevant in all countries of the world, since it cannot be completely eradicated in any country in the world, therefore one or another measures are taken to reduce it (voluntary and forced). For Ukraine, the question of the existence of tax debt is particularly relevant, as its volume increases annually.The article is devoted to deepening the theoretical foundations of the tax debt, highlighting its essential characteristics, as well as conducting an analysis of the tax debt in Ukraine and determining the reasons for its growth.The specificity of the scientific tasks, which are the subject of the research, required the use of a complex of special methods, the application of which helped to analyze the essence of the tax debt, to isolate its specific characteristics, and to conduct an analysis of its dynamics and structure in Ukraine.The article considers approaches to the interpretation of the content of tax debt. The first approach is based on domestic legislation, national accounting standards and the inevitable onset of liability for violation of tax discipline. The second approach is based on the behavior of the taxpayer, who makes a conscious decision to not pay his tax liability and takes responsibility for the violation of tax legislation in the form of fines and penalties. The author's definition of tax debt is proposed, which not only defines its content, but also contains the reasons and consequences of its existence. The essential characteristics of the tax debt, which relate to the non-fulfillment of the tax obligation by taxpayers, the reasons and results of its non-fulfilment, the need to agree on the monetary obligations of taxpayers, as well as the consequences of the existence of a tax debt for all participants in tax relations, are substantiated.As a result of the conducted analysis, it was established that in recent years in Ukraine, despite the constant improvement of tax legislation and the simplification of tax administration procedures, tax debt continues to accumulate. It was established that in order to reduce the amount of tax debt, it is necessary to carry out various measures of influence on taxpayers by the controlling bodies. For honest taxpayers, it is worth applying incentive measures in the form of exemption from tax audits for a certain period, and for dishonest taxpayers who have a tax debt, it is advisable to increase the responsibility for committing an offense.
Keywords: taxes; tax revenue; tax liability; monetary liability; interest; tax debt; regulatory bodies